Evaluasi Perangkat Lunak Pembelajaran Berbantuan Komputer (PBK): Suatu Survai di DKI Jakarta tahun 1993 - Yuliatri Sastrawijaya (Universitas Negeri Malang, 2016)
This study is aimed at knowing the relevance between the commercial Computer Assisted Instruction software and the principles of learning theories as well as the principles of communication in designing and develoving instructional materials. This study is a survey conducted in DKI Jakarta 1993. The population comprises CAI software for Natural Sciences, Social Sciences, and Languages numbering 12 in all. These 12 CAI software of 7 tutorial and 5 sets of material for drill. The result of the study showed that in general the Computer Assisted Learning softwares studied were categorized as being good. Further examination of each component revealed that on the average the objectives component on tutorial as well as that on drilling is graded as inappropriate. Other components such as the pedagogical content, technical design, and implementation support are categorized as appropriate.